2017
DOI: 10.1016/j.jinf.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of herpes zoster amongst adults varies by severity of immunosuppression

Abstract: Our results show that immunocompromised individuals are affected by the disease in particular and that the burden of herpes zoster is highest in severely immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 38 publications
2
47
0
3
Order By: Relevance
“… 6 Here, PHN was identified based on diagnosis codes whereas other studies used algorithms combining PHN diagnosis codes and/or pain medication prescriptions. 29-31 The conservative approach used here may have led to an underestimation of PHN in certain IC populations. We used an equally conservative approach to identify HZ-related complications other than PHN.…”
Section: Discussionmentioning
confidence: 90%
“… 6 Here, PHN was identified based on diagnosis codes whereas other studies used algorithms combining PHN diagnosis codes and/or pain medication prescriptions. 29-31 The conservative approach used here may have led to an underestimation of PHN in certain IC populations. We used an equally conservative approach to identify HZ-related complications other than PHN.…”
Section: Discussionmentioning
confidence: 90%
“…The reason relies on the fact that VZV-specific, cell-mediated immunity declines with age or immunosuppression, and it is the adaptive T cell response that is crucial for preventing the reactivation of the latent virus [ [7] , [8] , [9] ]. A recent study demonstrated that the incidence of herpes zoster was twice as high in immunocompromised than in immunocompetent hosts, and that higher incidences were observed among individuals with severe immunosuppression [ 10 ]. Higher incidences were also observed among women and older patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the incidence of herpes zoster was twice as high in immunocompromised than in immunocompetent hosts, and that higher incidences were observed among individuals with severe immunosuppression [ 10 ]. Higher incidences were also observed among women and older patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, where varicella vaccination has not been implemented, over 95% of the population is infected with VZV before the age of 6 years [ 2 ]. The average incidence of HZ in the Netherlands was 520 per 100,000 person-years in the period 2012–2015, and older age and a compromised immune system are the most important risk factors [ 1 , 3 , 4 ]. However, given the ageing population, it is expected that the incidence of HZ will increase in the near future [ 5 ].…”
Section: Introductionmentioning
confidence: 99%